Networks of Hate: The Alt-right, "Troll Culture", and the Cultural Geography of Social Movement Spaces Online. Issue 4 (7th August 2020) - Hodge, Edwin; Hallgrimsdottir, Helga
ABSTRACT: The "alternative right" or "alt-right" is a quintessentially twenty-first century phenomenon: a radicalized far right ideology that is proliferated and disseminated almost exclusively online with members drawn from all over the world. This paper argues that online debates within alt-right online communities about the acceptability of alt-right language and imagery are claims-making exercises that constitute examples of bordering processes. These debates establish cultural borders around online communities and foster new virtual geographies of counter-hegemonic movements of the far right, that transcend and challenge the role and relevance of the physical border as a container for these movements. The paper concludes by placing these findings within current theoretical framings of the a-territorial border, with particular attention to what implications these have for the Pacific Northwest.